PENGUKURAN PENGARUH BELANJA DESA TERHADAP KINERJA PEMBANGUNAN DESA DENGAN MENGGUNAKAN GEOGRAPHICALLY WEIGHTED REGRESSION - Eka Purna Yudha; Bambang Juanda; Lala M Kolopaking; Rilus A Kinseng (TATALOKA, 2018)
In 2014, the Government enacted Law No. 6/2014 on Villages with a view to reconstructing village financial and asset management arrangements to accelerate the inclusive and sustainable development of rural areas. The purpose of this study is to analyze the influence of village financial management on the performance of rural development. The study was conducted on 326 Villages in Pandeglang District. The analytical tool of the study using Geographically Weighted Regression (GWR) modeling will look at how the village expenditure is included in the Village Revenue and Expenditure Budget (APBDes). Expenditure of development (infrastructure) of the village has the greatest impact on the performance of village development with the value of elasticity of 0.637. The influence of village expenditure on the GWR model is strongly influenced by the geographical, demographic, and socio-economic conditions of rural communities, resulting in varying outcomes in each village.